O princípio do devido processo legal e sua aplicação na execução fiscal - Barra Neto, Paulo (2002)
This dissertation is about the importance of principie of due process of law. And its application in the revenue execution. In this opportunity, other constitutional and infraconstitutional principies that belong to execution process were studied. The principies presented in this dissertation have as objective to establish the necessary reciprocai relationship, respecting the principies pertinent to right democratic State The study of the principies that direct the process of the revenue execution was considerated observing especially the constitutional principies and its application in the fact and the norm, the obligation of the technical defense, the general principies of the process and the fiscal administrative. All the aspects were considerated to get the plenitude of the execution, respecting the Citizen in his ample right of defense. The source was taken by reading law, publications of national doutriners and congress. It’s observed that in spite of the brief procedure, the actual system of revenue execution doesn’t exclude the application of the due process of law, so it is evident its importance.